200-year industrial archaeological record preserved in an Isle of Man saltmarsh sediment sequence: Geochemical and radiochronological evidence. (30th April 2019) - Croudace, Ian W.; Teasdale, Phillip A.; Cundy, Andrew B.
Abstract: The Isle of Man, situated in the central Irish Sea, was a significant centre for Pb and Zn mineral extraction during the Industrial Revolution. Comminuted mining debris from the East Snaefell and North Laxey mining areas was transported, through hydrological action, from upland catchments to the coast. This study focuses on an eastern coastal sediment sink and a salt marsh sediment sequence from Port Cornaa. A sediment monolith was excavated, sub-sampled and geochemically investigated using Itrax scanning, WD-XRF analysis and radionuclide methods. Since the island is only 55 km from one of the world's major nuclear reprocessing sites (Sellafield), it was anticipated that a record of these radionuclide discharges (1951-present) would be identifiable and contribute clear chronological markers. The 137 Cs profile shows a Sellafield discharge component and also a larger component that is attributed to the 1986 Chernobyl airborne plume. This contribution in the salt-marsh sediment would be derived from the erosion and transport of Chernobyl-labelled upland soils into the marsh. Sediment depth was converted to age using natural ( 210 Pb) and anthropogenic radionuclides ( 137 Cs and 239, 240 Pu) and a compelling age vs depth relationship was obtained. The ability to reliably date the overall sediment section shows that sediment accumulation is uniform for the top 25 cm (5 mm/y) and from −25 to −70 cm (3.2 mm/y). The robust age-depth model allows features in the geochemical profiles for S, As, Pb, Zn and Cu to be dated and used to infer events at the East Snaefell and North Laxey mines. These include start-up of mining, introduction of more-efficient mining practises (i.e. water-wheel technology), change in the intensity of mining and final mine closure. The study provides a 200-year industrial archaeological record for the east coast of the Isle of Man. It demonstrates the benefits offered by a combined study involving non-destructive, high resolution Itrax scanning, conventional WDXRF and radionuclide dating.